Pathogenetic links between cognitive impairment in arterial hypertension and anatomical and functional characteristics of hippocampal morphology and blood supply (a literature review) - A. O. Svitlytskyi; I. F. Bielenichev; O. V. Hancheva; T. A. Hrekova (Patologìâ)
Aim. To update the study on morphological changes in the hippocampal structure and blood supply in conditions of persistent arterial hypertension with a focus on the cognitive sphere state.